Penelusuran Informasi Ilmiah Mahasiswa di Perpustakaan Universitas Lancang Kuning - Winda Monika; Vita Amelia; Triono Dul Hakim (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
Big data causes information explosion on the Internet where abundant information is provided every second. This phenomenon raises the problem of how to get precise, accurate, and reliable information out there. In addition, the ethics of using the information on the Internet also needs to be understood to minimize plagiarism. The University Library plays an important role in providing scientific information for the user. The university library should be able to provide references as well as educate its users on how to access and use those scientific information resources correctly. This Community Service (P2M) partnered with the Universitas Lancang Kuning Library aims to provide understating to librarians and students in information retrieval specifically the ability to identify, explore, access, and use scientific information appropriately. Keywords: information retrieval, information behavior, big data, Internet